Micro CT analysis of amount of dentin removal created by SAF vs. ProTaper systems - Diyar K Bakir; Hussain F Al-Huwaizi; Raid F Salman (College of Dentistry/ University of Baghdad, 2014)
Background: Dentin removed during root canal system instrumentation for creating adequate geometry for the canal and cleaning the canal. A new instrument had been marketed with the aim of optimum shaping of all parts of the canal system, however, no information present about the amount of dentin removal compared to conventional rotary system. This study investigated the amount of dentin removal when the canal instrumented by SAF compared with ProTaper by using high resolution computed tomography (micro CT). Materials and Methods: Twenty extracted single canalled teeth were utilized for this study; and randomly divided into 2 groups. In the first group, the root canals were prepared by using protaper rotary system till F2 and the root canal irrigated with 1ml of normal saline after each instrument. The root canals in the second group were prepared using SAF for 2min, with continuous irrigation (normal saline). After rescanning, the amount of dentin removal was calculated. Result: It was clear that the use of SAF system had increase the amount of dentin removal and in quantity larger than that did by ProTaper system & the mean of net difference was (0.288mm ± 0.051). By using t-independent test, there was highly significant difference between the two groups at (p=0.001), with in favor of the SAF system over ProTaper system at p< 0.01; in dentin removal quantity Conclusion: Root canal preparation with SAF-system resulted in more and effectively removed dentin when compared with protaper rotary files.